Clinically relevant hydrogel‐based on hyaluronic acid and platelet rich plasma as a carrier for mesenchymal stem cells: Rheological and biological characterization - Vadalà, Gianluca; Russo, Fabrizio; Musumeci, Maria; D'Este, Matteo; Cattani, Caterina; Catanzaro, Giuseppina; Tirindelli, Maria Cristina; Lazzari, Lorenza; Alini, Mauro; Giordano, Rosaria; Denaro, Vincenzo (Journal of orthopaedic research, 2017)
ABSTRACT Intervertebral disc regeneration is quickly moving towards clinical applications. However, it is still missing an ideal injectable hydrogel to support mesenchymal stem cells (MSC) delivery. Herein, a new injectable hydrogel composed of platelet rich plasma (PRP) and hyaluronic acid (HA) blended with batroxobin (BTX) as gelling agent, was designed to generate a clinically relevant cell carrier for disc regeneration. PRP/HA/BTX blend was tested for rheological properties. Amplitude sweep, frequency sweep, and rotational measurements were performed and viscoelastic properties were evaluated. Human MSC encapsulated in PRP/HA/BTX hydrogel were cultured in both growing medium and medium with or without TGF‐β1 up to day 21. The amount of glycosaminoglycan was evaluated. Quantitative gene expression evaluation for collagen type II, aggrecan, and Sox 9 was also performed. Rheological tests showed that the hydrogel jellifies in 15 min 20°C and in 3 min at 37°C. Biological test showed that MSCs cultured in the hydrogel maintain high cell viability and proliferation. Human MSC within the hydrogel cultured with or without TGF‐β1 showed significantly higher GAG production compared to control medium. Moreover, MSCs in the hydrogel underwent differentiation to chondrocyte‐like cells with TGF‐β1, as shown by histology and gene expression analysis. This novel hydrogel improves viability and proliferation of MSCs supporting the differentiation process toward chondrocyte‐like cells. Rheology tests showed optimal gelation kinetics at room temperature for manipulation and faster gelation after transplantation (37°C). The clinical availability of all components of the hydrogel will allow a rapid translation of this regenerative approach into the clinical scenario. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:2109–2116, 2017.